2020
DOI: 10.1093/femsyr/foaa036
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis reveals MAPK signaling pathways affect the autolysis in baker's yeast

Abstract: Abstract Yeast autolysis refers to the process in which cells degrade and release intracellular contents under specific conditions by endogenous enzymes such as proteases, nucleases and lipid enzymes. Protein-rich baker's yeast is widely used to produce yeast extract in food industry, however, the molecular mechanism related to baker's yeast autolysis is still unclear. In this study, RNA-seq technology and biochemical analysis were performed to analyze the autoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Autolysis is a ubiquitous process in eukaryotic cells, in which cells degrade and release intracellular content responding to internal and external stress factors [ 15 ]. As is well known, fungal autolysis occurs at the global-cell level and involves various enzymological profiles (proteases, nucleases, and lipid enzymes), signal pathways, and morphological changes [ 9 , 26 ]. The P. pastoris morphological changes induced by the AMP in the current study, such as the lesser cell number and the larger cell size, were similar to the previous study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Autolysis is a ubiquitous process in eukaryotic cells, in which cells degrade and release intracellular content responding to internal and external stress factors [ 15 ]. As is well known, fungal autolysis occurs at the global-cell level and involves various enzymological profiles (proteases, nucleases, and lipid enzymes), signal pathways, and morphological changes [ 9 , 26 ]. The P. pastoris morphological changes induced by the AMP in the current study, such as the lesser cell number and the larger cell size, were similar to the previous study.…”
Section: Resultsmentioning
confidence: 99%
“…In the baker’s yeast Saccharomyces cerevisiae , the DEGs under the autolysis condition were significantly enriched in the MAPK signaling pathway, and they were all expressed in a down-regulated form. This study suggested that the MAPK signal pathway plays an important role in the yeast autolysis process, and that autolysis inhibits the activity of yeast cells in energy production and utilization [ 9 ]. In the current study, almost all of the DEGs related to the MAPK signal pathway were inhibited during the autolysis of the P. pastoris , indicating that the MAPK signal pathway regulated the autolysis process closely, and that the cell activity was inhibited at the global level during autolysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S5). MAPK signaling pathway reflects adaptive responses to extracellular and intracellular conditions by regulating basic cell functions [ 30 ]. In this study, the extracellular conditions of MttA did not change, but the changes were from intracellular regulation.…”
Section: Discussionmentioning
confidence: 99%